Fifth Grade Students’ Creative Thinking in Solving Open-Ended Mathematical Problems - Madha Lely; Zetra Hainul Putra; Syahrilfuddin Syahrilfuddin (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2020)
The purpose of this study is to find out how fifth-grade students apply creative thinking abilities to solve open-ended mathematical problems. The study was conducted with 19 fifth grade students from a public school in a rural area, Kampar, Indonesia. The data were collected by giving 10 open-ended mathematical problems on whole numbers, fractions, and geometry and measurement. Creative thinking abilities of fifth-grade students in solving open-ended mathematical problems view from three indicators; fluent thinking, flexible thinking and original thinking. The results show that the average ability of students’ creative thinking was 23.68. This means that students’ creative thinking was poor or less creative.